Meningkatkan kemampuan berpikir kreatif matematis siswa MTs melalui pendekatan problem solving berbantuan geogebra - Kharisma, Wafa; Hutajulu, Masta; Amelia, Risma (IKIP Siliwangi, 2025)
This study aims to determine the effectiveness of the implementation of the GeoGebra-assisted Problem Solving approach on the mathematical creative thinking ability of MTs students. This study used a mixed methods with a Convergent Parallel design. Quantitative data were obtained through pretest and posttest tests, while qualitative data were obtained through student response questionnaires. The research subjects consisted of two classes, namely the experimental class and the control class, each consisting of 25 students. The research instruments included a descriptive test of mathematical creative thinking ability and a student response questionnaire. The t-test results showed a significant difference between the posttest results of the experimental class and the control class with a significance value of 0.001 < 0.05, which means that the implementation of the GeoGebra-assisted Problem Solving approach had a positive effect on improving students' mathematical creative thinking ability. In addition, the questionnaire results showed a very positive response to the implementation of this approach on the indicators of motivation, understanding, interest, and activeness. Thus, the GeoGebra-assisted Problem Solving approach can encourage students' creativity, activeness, and conceptual understanding in mathematics learning.